Significance of the peripheral blood Treg/Th17 ratio as a prognostic immune biomarker in newly diagnosed multiple myeloma and its correlation with 1q21 gain/amplification - Wen, Jingjing; Zhou, Qiaolin; Xu, Fang; Yue, Jing; Zhang, Ya; Liu, Yiping; Su, Jing; Liang, Xiaogong (Frontiers in Immunology, 2025)
BackgroundRegulatory T (Treg) and T helper 17 (Th17) cells play opposing roles in immune responses, and their balance critically regulates the multiple myeloma (MM) microenvironment. Despite advances in immunotherapy, current risk stratification lacks immune biomarkers.MethodsWe collected the peripheral blood and bone marrow samples from MM patients to investigate the relationships among 1q21 gain/amplification, the Treg/Th17 ratio, and MYC gene abnormalities at diagnosis, remission, and relapse. Additionally, we evaluated the prognostic impact of the Treg/Th17 ratio.ResultsA total of 130 newly diagnosed MM patients were enrolled, with 82 patients evaluated for 1q21 gain/amplification. During remission, patients with 1q21 gain/amplification had a significantly higher Treg/Th17 ratio (1.59 vs. 0.85, P = 0.042) and MYC expression levels (70.54% vs. 32.76%, P = 0.042) compared to those without 1q21 gain/amplification. Furthermore, patients with an elevated Treg/Th17 ratio (>0.7) during remission exhibited slightly higher MYC expression (45.70% vs. 30.60%) than those with lower ratios (P = 0.451). Patients achieving partial response or better exhibited significantly higher Th17 levels (3.34%, range: 0.19–10.80%) at diagnosis compared to those without remission (0.29%, range: 0–2.18%, P = 0.033). The group of elevated Treg/Th17 ratio (> 1.0) at diagnosis exhibited significantly shorter PFS compared to the reduced ratio (≤ 1.0) group (13.87 months vs. 30.67 months, P = 0.006). R2-ISS staging showed no significant impact on PFS (P = 0.236). By assigning scores to R2-ISS stages and elevated Treg/Th17 ratio at diagnosis, patients were stratified into low-risk (1–3 scores) and high-risk (4–5 scores) groups. High-risk patients exhibited significantly worse PFS compared to low-risk patients (P = 0.022). The combined model integrating R2-ISS staging and Treg/Th17 ratio achieved a concordance index(C-index) of 0.8, surpassing the C-index of R2-ISS staging alone (0.562), demonstrating better predictive performance.ConclusionA potential mechanistic connection exists between 1q21 gain/amplification and immunosuppression, and the role of the MYC gene in this mechanism has garnered substantial interest. Patients with a higher Treg/Th17 ratio at diagnosis are more prone to relapse. The combination of R2-ISS staging and the Treg/Th17 ratio at diagnosis demonstrates stronger predictive ability for relapse.